Mechanistic studies of DepR in regulating FK228 biosynthesis in Chromobacterium violaceum no. 968 - Qiao, Yongjian; Tong, Tiantian; Xue, Jiao; Lin, Wenjing; Deng, Zixin; Cheng, Yi-Qiang; Zhu, Dongqing (PLOS ONE, 2018)
DepR, a LysR-type transcriptional regulator encoded by the last gene of the putative min operon (orf21-20-19-depR) located at the downstream region of the anticancer agent FK228 biosynthetic gene cluster in Chromobacterium violaceum No. 968, positively regulates the biosynthesis of FK228. In this work, the mechanism underlining this positive regulation was probed by multiple approaches. Electrophoretic mobility shift assay (EMSA) and DNase I footprinting assay (DIFA) identified a conserved 35-nt DNA segment in the orf21-orf22 intergenic region where the purified recombinant DepR binds to. Quantitative reverse transcription PCR (RT-qPCR) and green fluorescent protein (GFP) promoter probe assays established that transcription of phasin gene orf22 increases in the depR deletion mutant of C. violaceum (CvΔdepR) compared to the wild-type strain. FK228 production in the orf22-overexpressed strain C. violaceum was reduced compared with the wild-type strain. DepR has two conserved cysteine residues C199 and C208 presumed to form a disulfide bridge upon sensing oxidative stress. C199X point mutations that locked DepR in a reduced conformation decreased the DNA-binding affinity of DepR; T232A or R278A mutation also had a negative impact on DNA binding of DepR. Complementation of CvΔdepR with any of those versions of depR carrying a single codon mutation was not able to restore FK228 production to the level of wild-type strain. All evidences collectively suggested that DepR positively regulates the biosynthesis of FK228 through indirect metabolic networking.